NASKAH KUNO MELAYU RIAU SEBAGAI SUMBER PENCIPTAAN KARYA SASTRA MASA KINI - Junaidi, Junaidi (Universitas Lancang Kuning, 2010)
Old manuscript is one of important cultural heritages in Malay civilization.